Comparison of two drospirenone-containing oral contraceptives for their effect on the ovary, menstrual cycle, acne, and side-effect profile: 20 µg ethinylestradiol/3 mg drospirenone (24/4) versus 30 µg ethinylestradiol/3 mg drospirenone (21/7) - Tekeli Taşkömür, Aysun; Erten, Özlem; Dilbaz, Berna (Journal of Surgery and Medicine, 2021)
Background/Aim: Serious side effects, depending on the length of the hormone-free interval and the estrogen dose, cause the discontinuation of combined oral contraceptives (COCs). Therefore, it is important to identify COCs with minimal side effects which provide effective contraception. This study aimed to compare the effects of two different drospirenone-containing oral contraceptives (COCs) on ovarian suppression, cycle control, premenstrual symptoms, pain, acne, and the incidence of side-effects. Methods: This prospective randomized controlled study was conducted with eighty women aged between 17-40 years. Patients were randomized to either 3mg drospirenone/30mcg ethinylestradiol (21/7 tablets) (Group 1) or 3mg drospirenone/20mcg ethinylestradiol (24/4 tablets) (Group 2) COCs. On Day-3 of the pre-treatment cycle, menstrual cycle patterns, serum hormone and lipid levels, menstrual complaints were recorded, followed by an evaluation of Day-21 progesterone levels, sonographic evaluation of endometrial thickness and the ovaries. Same assessment was repeated after pill use and the findings of the two cycles were compared. Results: Both COC formulations suppressed serum hormone levels, decreased endometrial thickness and reduced incidence of dysmenorrhea-dyspareunia, and acne while serum HDL-cholesterol level was increased. Progesterone, FSH and endometrial thickness were lower, and serum cholesterol level was higher in Group 2 (P=0.007, P=0.044, P<0.001, P=0.035; respectively). Breast tenderness was significantly less in Group 2 (P=0.02). The incidence of follicular development, menstrual irregularity, and a headache was higher in Group 1, but the difference was not significant except for headaches (P=0.027). Conclusion: 24/4 tablets might be a better alternative to 21/7 tablets with the advantage of tolerability as well as providing effective contraception.